Discovering Competency’s Elements in the Affective Domain of a Sustainable Co-curricular Syllabus - Puddin, Azli; Ibrahim, Badaruddin; Ismail, Mohd Firdaus (International Journal of Sustainable Construction Engineering and Technology, 2023)
Developing a sustainable co-curricular syllabus incorporating competency elements across all three learning domains - cognitive, psychomotor, and affective is challenging. However, this paper focuses on the affective domain, crucial in shaping students’ personalities and forming positive values. The study presented here aims to identify the competency elements required for the affective domain in developing the co-curricular Silat syllabus. This study employed a qualitative research method and gathered data through interview sessions with six Silat experts from PESAKA Malaysia. The experts were asked open-ended questions to guide their opinions on the competency elements in the affective domain. The interview sessions were conducted in an organised workshop where the experts were briefed on the purpose of the interview. The information revealed by the experts was recorded, transformed into transcripts, and analysed using the thematic method. The study’s findings revealed that the competency elements required for the affective domain in the co-curricular Silat syllabus are good values, civility, athletic abilities, respect, and morality. These elements are vital in the affective learning domains that shape the personality and competency of the students in their co-curricular subjects. The identified competency elements for the affective domain in the co-curricular Silat syllabus will aid in shaping students’ personalities, forming positive values, and improving their abilities. It is recommended that further studies be conducted to identify competency elements in the cognitive and psychomotor domains, which will contribute to developing a comprehensive and sustainable co-curricular syllabus.